PENGARUH EMOTIONAL QUOTIENT TERHADAP AKHLAK SISWA DI MTS AL ITTIHADIYAH KOTA MEDAN - Novita Sari, Nindi; Sahyan, Sahyan (Fakultas Agama Islam, 2023)
School is a place where children learn to interact with other people. Schools must build a culture that prioritizes moral aspects, love, gentleness, respect for differences, and abstain from violent attitudes. Schools must improve emotional intelligence which influences students' moral factors (behavior) in order to achieve quality education. This research uses quantitative descriptive analysis techniques, namely statistics. Data collection uses the following techniques, questionnaires, observation, interviews and documentation. Emotional Quotient has a great influence on student morals. This is based on the results of analysis using a simple linear regression formula and obtained Fcount results of 138.555 with a significance level of 0.000 which is smaller than 0.05. From the test results, it is known that the influence of emotional quotient on student morals is 61.2%, this shows that there is still 38.8% influence from other variables that were not examined in this research. From the results of the coefficient of determination test with a correlation coefficient R of 0.782, it is concluded that the influence of emotional quotient on student morals is strong.